Towards a Poelitics of the Tragedy of State The Raison d'État in Shakespeare's Hamlet and Ben Jonson's Sejanus His Fall - Aloui Amira (2023)
The present research will study the poelitics of the Tragedy of State in relation to the politico-philosophical discourse of Reason of State. I will be introducing the new genre of the Tragedy of the State and argue for its poelitics. I will, also, be introducing the discourse of Reason of State to the literary scholarships of Shakespeare, Ben Jonson, and their contemporaries. The emerging early modern philosophical discourse has remained a gap in the scholarship despite its importance, not to say centrality, in political thought and the history of ideas. The two plays under study in the present research are Shakespeare’s Hamlet and Ben Jonson’s Sejanus His Fall. In addressing the emerging political thought in England and the continent, I will argue for a revisitation of the two plays that can only be possible with acknowledging the importance of Reason of State. As the title of my work indicates, reading the plays through this historically informed critical perspective will allow for the understanding of a new poelitical form that has long been dismissed as marginalia.